2016
DOI: 10.1002/nau.23175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of levator ani muscle throughout the different stages of labor by transperineal 3D ultrasound

Abstract: We conclude that the phase of delivery that causes a major increase in the area of the levator hiatus area and in the levator ani muscle area is when the fetal head reaches the 4th plane of Hodge. Furthermore, data in our paper indicates that the exact moment in which the avulsion of the levator ani muscle is produced is when the bulging of the fetal head on the maternal perineum occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
0
20
0
2
Order By: Relevance
“…We observed that deliveries with disengagement of the branches of the forceps before extraction of the fetal head show a similar rate of LAM avulsion with an adjusted OR (without disengagement vs with disengagement) of 0.82 (95% CI 0.40‐1.69; P = 0.603). Hence, in deliveries without disengagement, we did not identify any statistically significant increase in the rate of LAM injuries due to the increase in the levator hiatus area because of the association of the fetal head and forceps during the passage of the fetal head at the level of the LAM, during which women are more susceptible to injuries . The increase in the area of the hiatus during the passage of the fetal head in cases of non‐disengagement of the forceps may also suggest the hiatal overdistensibility (microtrauma) that we observed in our study in cases of non‐disengagement …”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…We observed that deliveries with disengagement of the branches of the forceps before extraction of the fetal head show a similar rate of LAM avulsion with an adjusted OR (without disengagement vs with disengagement) of 0.82 (95% CI 0.40‐1.69; P = 0.603). Hence, in deliveries without disengagement, we did not identify any statistically significant increase in the rate of LAM injuries due to the increase in the levator hiatus area because of the association of the fetal head and forceps during the passage of the fetal head at the level of the LAM, during which women are more susceptible to injuries . The increase in the area of the hiatus during the passage of the fetal head in cases of non‐disengagement of the forceps may also suggest the hiatal overdistensibility (microtrauma) that we observed in our study in cases of non‐disengagement …”
Section: Discussionmentioning
confidence: 62%
“…The most critical time for LAM avulsion is when the fetal head reaches the perineum and the levator hiatus area is largest . We believe in the importance of caution at this time and the least trauma possible.…”
Section: Introductionmentioning
confidence: 92%
“…40 The levator ani muscle injury rate in vacuum deliveries described in this paper is similar to that described in our previous studies. As we believe that crowning is the moment at which levator injury is more likely to be produced, 18 special care was taken at this moment of the delivery. No significant differences were observed between the rate of levator ani muscle injury after vacuum deliveries and forceps deliveries.…”
Section: Malmström Vacuum and Kielland Forceps Deliveriesmentioning
confidence: 99%
“…16 These alterations, associated with a decrease in strength and with age-related fibrosis, represent the probable mechanisms for pelvic floor muscle dysfunction in elderly women. 18 The levator ani muscle manages to stretch more than three times its usual length to allow the exit of the fetal head. 18 The levator ani muscle manages to stretch more than three times its usual length to allow the exit of the fetal head.…”
Section: Introductionmentioning
confidence: 99%
“…The pelvic floor undergoes a series of changes during labour that can lead to the avulsion of the levator ani muscle (LAM) . This traumatic disconnection of LAM from its insertion at the pubic level causes the muscle to become more distensible and less contractile .…”
Section: Introductionmentioning
confidence: 99%